Republican Arthrology Center and its contribution to the development of orthopedic rheumatology - Grishin, Sergey E.; Puchinyan, Daniil M.; Fedonnikov, Alexander S.; Ostrovsky, Vladimir V.; Norkin, Igor A. (Saratov Medical Journal, 2021)
The article provides information on the organization and functioning achievements of the Republican Arthrology Center (RAC), which has become the first specialized clinic in the Russian Soviet Federative Socialist Republic (RSFSR) that provided arthrological assistance to the population. The result of the organizational and methodological efforts of the RAC employees was the development of a network of rheumatology rooms in almost all territories of the country, along with the organization of the orthopedic rheumatology service and its separation from the cardiovascular rheumatology service. In the RAC, scientific developments were successfully carried out on the problems of arthroplasty of large joints, surgical and conservative treatment of patients with rheumatoid arthritis, osteoarthritis of large joints, prevention of contractures of the knee joint. Saratov Research Institute of Traumatology and Orthopedics (SRITO) hip joint endoprosthesis, a collapsible endoprosthesis and other constructions that have received wide recognition were created at the RAC. In the absence of international experience in creating an orthopedic rheumatology service network, the RAC was, on one hand, a pioneering phenomenon in world health care, and on the other hand, a natural consequence of the power vertical centralization in the USSR. At the same time, it should be emphasized that the need to create the RAC in the Russian Federation was caused by the growth in morbidity of rheumatic diseases, along with population aging and the prospects of orthopedic rheumatology associated, first of all, with the active introduction of total joint replacement with artificial structures in developed countries of the world. Over three decades of its existence, the RAC has been an organizational, methodological, medical, scientific and consulting center providing an orthopedic care to patients with diseases and injuries of large joints throughout the Russian Federation.